From New Public Management to New Public Governance? Hybridization and Implications for Public Sector Consumerism. (May 2014) - Wiesel, Fredrika; Modell, Sven
Abstract This paper examines how variations in the notion of public sector consumerism become embedded in diverse governance practices. To this end, we extend the literature on public governance logics with insights from research on public sector consumerism and hybridization in public sector management reforms. Through a comparative, multi‐level analysis we trace the development of two governance logics largely corresponding to the distinction between New Public Management (NPM) and New Public Governance (NPG) in Swedish transport infrastructure policy. In contrast to research predicting or prescribing a relatively radical shift between such governance logics we show how they partly co‐evolved along two reform paths entailing notable variations in the degree of hybridization and the embedding of consumerist notions in emerging governance practices. In doing so, we draw attention to how the hybridization of governance logics is contingent on the alignment of diverse interests and differences in the process through which such logics are brought together. We discuss the implications of these findings for future research into public sector consumerism and hybridization in public sector management reforms.